O jogo e a educação física em uma instituição de educação especial - SOARES, Mariana do Nascimento (2022)
Gambling as an element of culture is present in various civilizations and their assigned meanings depending on society and social context. Gambling is an action that predates even civilization. Education uses the game as a teaching resource for the contributions resulting from its use. We can highlight here: motor, cognitive, psychological development, sociability, intelligence, reasoning, agility, affection, among others. Just as regular education has already recognized the benefits of gambling in the teaching and learning process, Inclusive and Special Education has begun to include playful activities in the content and methodologies developed with students with disabilities. Departing from the need to investigate the relationship that the game has with Inclusive Physical Education, the research problem arises: What is the importance of games in Inclusive Physical Education. The general objective of the research is: to investigate the game in Physical Education in a Specialized Education Unit. As specific objectives, it was delimited: a) to identify the types, materials, methodologies and evaluation processes used to approach the game content; b) understand the importance attributed to the game by the teachers interviewed; c) reflect on the limits and possibilities of game content in special Physical Education. From the analysis it was possible to identify the importance that the game assumes in allowing the student with disabilities not only to participate in the teaching and learning process, but also to become an active agent in the process. Able to act with its limitations, no longer being a passive student who was not seen as able to develop skills present in his actions. Being able to acquire important social notions for relationships in the community in which the student lives.